Graph-based representation of design properties in creating building floorplans. (February 2018) - Ślusarczyk, G.
Abstract: This paper proposes a framework for supporting the design process by defining design requirements over graph-based representations of designs. First, hierarchical layout hypergraphs ( HL -graphs) representing designs and hierarchical layout graph grammars generating them are specified. Then, local and global graph requirements over HL -graphs, which correspond to design constraints, are defined. The proposed ontological interpretations transform first-order and monadic second-order logic formulas expressing design criteria into equivalent local and global graph requirements. The satisfiability of graph requirements by representations of designs allows for checking correctness of design solutions. The approach is illustrated on examples of designing floor layouts of buildings. Highlights: Hierarchical graphs representing designs and grammars generating them are defined. Local and global requirements over graph representations of designs are specified. The proposed interpretations transform logic formulas into graph requirements. The satisfiability of graph requirements by representations of designs is tested. The approach is illustrated on examples of designing building layouts.